PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN KALITURI DAN DUSUN KALICANGAK DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , ANISA TAQIATUN B; , Ir.Parseno.ST , ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The final report explain about the surveying and land mapping to produce a map that provides information on the spatial data of the earth's surface. The method used is the measurement framework of horizontal control surveys, vertical control surveys, the measurement of planimetric detail, as well as the spot height , as well as digital imaging. The result is a situation map the Earth's surface in the form of spatial data location 2, village and hamlet kalituri kalicangak, village outs, freshman subdistrict, Klaten district, Central Java province with a scale of 1: 500 in sisitem projection UTM (Universal Transverse Mercator).